Evidence‐based practice and clinical reasoning in occupational therapy: A cross‐sectional survey in Chile. (10th December 2020) - Garcia, Jenniffer; Copley, Jodie; Turpin, Merrill; Bennett, Sally; McBryde, Catherine; McCosker, Josie Louise
Abstract: Introduction: Evidence‐based practice (EBP) is a critical framework for supporting clinical decision‐making that has been increasingly promoted in occupational therapy over the last 20 years. Discipline‐specific EBP frameworks and resources have emerged, primarily created by scholars from developed countries. However, EBP has received limited attention in literature published in developing and non‐English speaking countries. This study aimed to explore Chilean occupational therapists' perceptions of EBP, factors influencing the adoption of EBP and sources of information used to inform clinical decision‐making. Methods: A cross‐sectional online survey of Chilean occupational therapists included socio‐demographic information, closed questions using a fivepoint Likert scale and open‐ended questions. Numerical data were summarised using frequencies and percentages. Cross‐tabulations explored relationships between variables. Narrative data from openended responses were analysed deductively using content analysis. Results: Complete surveys were returned by 192 Chilean respondents. The majority of participants (68.3%) defined EBP as the use of research knowledge only and perceived EBP as useful and important. The most significant barriers to the application of research knowledge included: lack of time (68.2%), an emerging research culture (67.7%) and restricted access to scientific literature (56.8%). Additionally, Chilean occupational therapists did not feel confident finding, appraising and integrating research evidence. Of the four sources of knowledge used in EBP, participants predominantly relied on clinical observations of clients (99.5%), their clinical expertise (89.1%), and discussions with the multidisciplinary team (78.1%) and other occupational therapists (40.1%), to inform clinical decision‐making. Conclusion: Language barriers, lack of time, scarcity of locally produced research, and an emergent research culture within Chile impede occupational therapists' ability to implement EBP. The adoption of EBP can facilitate access to contemporary occupational therapy knowledge powerfully guide clinical reasoning, and build local research capacity. Building research partnerships and collaborations with the international scientific community are crucial to the global achievement of EBP.